Innovative approach using ultrasonic-assisted laser beam machining for the fabrication of ultrasensitive carbon nanotubes-based strain gauges. (February 2023) - Karimzad Ghavidel, Ayub; Zadshakoyan, Mohammad; Kiani, Gholamreza; Lawrence, Jonathan; Moradi, Mahmoud
Highlights: Creation a new surficial nanostructure on the CNT-based nanocomposite. Fabrication of ultrasensitive strain sensor with the gauge factor about 8 times higher than the best similar samples reported previously. Presentation of a novel combinatory process to adjust the surface electrical resistivity of nanocomposite. Abstract: Here, we present for the first time a novel process based on the simultaneous implementation of ultrasonic vibrations (USVs) and laser beam machining (LBM) to fabricate ultrasensitive strain gauges fabricated from polymethyl methacrylate (PMMA)/carbon nanotubes (CNTs) nanocomposites. The results clearly showed that ultrasonic-assisted laser cutting reduces the surface electrical resistance up to 2.5 kΩ, while laser cutting alone is able to reduce the surface electrical resistance down to 3 kΩ towards the best conditions. Microscopic studies confirm that USVs reduce the wrapping of PMMA chains around CNTs and intensify the mechanism of electrons transfer through tunneling by improving the dispersion degree of CNTs on the surface. It was found that the prepared sample using USVs with an 80 W laser power and the beam motion velocity of 35 mm/s presented the best performance for detecting small strains. The sensing properties of the generated sample were characterized in the strain range of 0–1.2%. At 1.2% strain, the relative resistance changes were 27.04%, indicating the gauge factor is higher than 20 for the fabricated strain gauge, which is about 8 times higher than the best similar samples reported previously.